The Permeable Character of CSG Dams and Their Seepage Fields. (14th October 2018) - Zhao, Xin; He, Yunlong
Abstract : Current studies regarding the permeable properties, corrosion properties, and seepage characteristics of cemented sand and gravel (CSG) materials are based on laboratory tests. Thus, there is a lack of studies analyzing the permeable character of seepage fields based on monitoring data from real prototypes working under practical operating conditions. In this paper, on the basis of measured data from the Dahuaqiao cofferdam, we establish an inversion analysis method for unsteady seepage fields covering different time periods within a time sequence. The results indicate an effective dynamic change law for the material permeability coefficient and the real dynamic evolution characteristics of seepage fields. The permeability coefficient of CSG exhibits a "self-healing" phenomenon similar to concrete, with the seepage characteristics of a dam tending to become stable over time. Under the long-term action of water pressure, the seepage behavior of the dam body shows no obvious deterioration, suggesting that CSG can satisfy the required anticorrosion property expected of dam construction materials. Thus, abnormal CSG might serve as an effective antiseepage layer that can meet the running requirements of cofferdams. The results of this research can provide reference for further improvement in the CSG dam design theory.